Comparative Behaviour of Soft Soil by Analysing The Parameters of Cone Penetration Test with Pore Water Pressure (CPTu) in Western Johor - Zuraini Zainal,; Adnan Zainorabidin,; Zeety Md Yusof,; Amirzaki Salikin,; Mohamad Johari Zainal,; Kasbi Basri,; Koh An Ang,; Paulus Pramono Rahardjo,; Ramli Nazir, (International Journal of Integrated Engineering, 2025)
Soft soil consists of marine clay, peat and organic soil with low strength, high compressibility and water content. This soil type poses persistent challenges for contractors, consultants, and designers during the design, construction, and maintenance stages. Even with modern advancements, it is still difficult to fully understand how soft soils in tropical areas behave. Significant environmental influence factors like high rainfall, warm temperatures, and complex soil compositions, make their behaviour unpredictable and hard to study. Therefore, conducting thorough in-situ site investigation work is crucial for the development area located in tropical regions. In-situ high-end measuring devices like the Cone Penetration Test with Pore Water Pressure (CPTu) provide highly efficiency in the characterization of sites, particularly those with distinct stratigraphic horizons. In this study, CPTu was performed to determine the CPTu parameters consisting of cone resistance (qc), sleeve friction (fs) and pore water pressure (u2). Three and two of the CPTu points were conducted in Pontian and Sedenak, Johor respectively. The CPTu parameters were analyzed to determine the behaviour and subsurface profiling. This study also compares CPTu values with those from a prior investigation in Parit Nipah, Johor, to clarify the diversity of soil behaviour and presents a range of CPTu parameters within the Western region of Johor. The findings exhibit the behaviour and identify the heterogeneous subsurface profiling which consists of layers of peat, soft and medium stiff clay by indicating the significant range of CPTu parameter values. Peat exhibits range for qc, fs and u2 of 0.001–0.890 MPa, 0.0006–0.033 MPa, and 0.0001–0.079 MPa, respectively. Meanwhile, soft clay demonstrates ranges of 0.056–0.850 MPa, 0.0001–0.006 MPa, and 0.011–0.255 MPa. Medium stiff clay reveals corresponding ranges of 0.150–6.480 MPa, 0.001–0.077 MPa, and 0.045–0.677 MPa. In conclusion, CPTu was able to identify behaviour of soft soil and its characterization, which is essential in designing a safe, economical and long-term lifespan of buildings and infrastructure.